ANALYSIS OF EFFECTIVE METHODS OF USING COMMUNICATIVE EXERCISES TO DEVELOP SPEAKING SKILLS IN PRIMARY SCHOOL ENGLISH CLASSES - Rizayeva Gulasal (International Journal of Literature and Language Studies, 2026)
This article examines the efficacy of communicative activities in enhancing speaking abilities among primary school English learners. Employing a qualitative study approach that integrates literature analysis, classroom observation, and teacher interviews, four primary techniques—role-play, information-gap activities, communicative games, and task-based collaborative projects—were analysed. A four-week intervention with 78 pupils yielded significant enhancements in fluency, confidence, vocabulary utilisation, and spontaneous speaking. The results show that communicative activities can generate meaningful, age-appropriate chances for engagement and greatly help spoken language development when there is enough assistance. Suggestions and effects on teaching practice are spoken about.